The Effect of Empowerment Training Program on Enhancing the Social Quality of Life for Mothers of Orphans - Al-jameel, Suhailah S.; Sakoury, Mona Mostafa Abdo; Alhammali, Azhar Saeed; Al Sabti, Nada Abdrabalredha; Alkhaldi, Thuraya Mufarrih (Journal of Posthumanism, 2025)
This study evaluated the effectiveness of a structured training program designed to enhance the quality of life for orphan mothers through comprehensive personal and professional skills development. The program addressed multiple domains, including mental health, psychological and social well-being, effective communication, behavior modification, family health awareness, prophetic approaches to child-rearing, educational follow-up for children, and the advancement of economic and managerial competencies.A pre–post experimental design was employed, involving 25 orphan mothers who participated in the program. Data were collected via structured questionnaires and analyzed using appropriate statistical methods to assess changes in participants’ perceptions and self-reported capabilities before and after the intervention.The results demonstrated notable improvements across all targeted dimensions. Mental health indicators showed significant alignment between subjective assessments and objective measures, reflecting enhanced psychological resilience. Similarly, participants reported higher satisfaction in meeting psychological and social needs following the program. Gains were also evident in effective communication and behavior modification skills, with weighted average scores increasing substantially.Further, participants exhibited heightened awareness of family health practices, stronger adherence to prophetic child-rearing principles, and more active engagement in children’s educational follow-up. Economic and managerial competencies also improved, particularly in time management, digital literacy, problem-solving, decision-making, résumé writing, legal literacy, and household budgeting.Overall, the program produced significant positive changes in the quality of life of orphan mothers, underscoring the value of integrated training interventions in addressing both personal development and socio-economic empowerment. These findings highlight the program’s potential as a replicable model for similar communities.